The Impact of External Pressure, Environmental Uncertainty, and Commitment of Management on Implementation of Financial Reporting Transparency - HARDO BASUKI; M. ARSYADI RIDHA (The Indonesian Journal of Accounting Research, 2013)
In Indonesia, studies on the implementation of financial reporting transparency are still very scarce and limited. Based on a survey conducted in the Special Region of Yogyakarta, the purpose of this study is to explore a conceptual model developed to explain the relationship between external pressures, environmental uncertainty, management commitment and in financial reporting transparency. The theoretical development and interpretation of this research is drawn from institutional theory. The samples for this study comprise 149 SKPD in the Special Region of Yogyakarta. This study uses mixed method, applying a combination of two approaches (quantitative and qualitative) at the same time with a sequential explanatory strategy. The Partial Least Square (PLS) method was used to analyze the proposed model and relationships. Content analysis was used to capture the phenomenon of isomorphism that occurred in implementation of the transparency financial reporting. This study provides evidence that the implementation of transparency in financial reporting in the Special Region of Yogyakarta is influenced by external pressures and management commitment. The major contribution of this research is to provide an understanding of the factors that affect the application of financial reporting transparency, which in turn could be used to formulate government policy in the future.